KONSEP INFLASI : PERBANDINGAN PEMIKIRAN IBNU KHALDUN DAN AL MAQRIZI SERTA IMPLIKASINYA DI INDONESIA - Alwa, Moh. Abdul Aziz; Wahyudi, Amin (Invest Journal of Sharia & Economic Law, 2022)
Inflation is a problem in the economic system that has occurred repeatedly from the beginning of the development of human civilization. Since people started using money to trade goods and services, inflation has remained constant. On the other hand, the inflation rate is also used as a macroeconomic analysis of a country/region, such as economic growth, external balance, and income distribution. Conditions of high inflation, if not handled thoughtfully and appropriately, will cause economic depression. However, in the Islamic world, there are scholars, namely, Ibn Khaldun and Al-Maqrizi. These two Muslim thinkers provide an overview of the phenomenon of inflation since the 14th century AD. This research seeks to find the slices of Ibn Khaldun and Al-Maqrizi's thoughts about the causes of inflation and to offer solutions to the phenomenon of inflation that occurs. We chose the literature study research to explore the thoughts of Ibn Khaldun and Al-Marqizi in classic books and several primary sources that discuss the thoughts of the two and compare them with the concept and conditions of inflation in Indonesia through the official websites of BPS and Bank Indonesia. The study found that a country's weak administrative system and corrupt mentality cause inflation. To overcome inflation, improving the two causes of inflation above is the solution offered by these two experts.